A study on students’ satisfaction towards the housing facilities at Apartment Pelajar Jalan Tun Ali (APJTA) / Mohd Irwan Wahab and Ahmad Farid Zainal - Wahab, Mohd Irwan; Zainal, Ahmad Farid (Faculty of Administrative Science and Policy Studies, 2012)
Service quality is a concept that has aroused considerable interest and debate in the research literature because of the difficulties in both defining and measuring it with no overall consensus emerging on either. Customer satisfaction and service quality are often treated together as functions of customer’s perceptions and expectations and research has shown that high service quality contribute significantly to profitability. Service quality is required to be first measured in order to improve the quality in a service organization. Practitioners and academics are eager on measuring service quality accurately in order to have better understanding of its indispensable antecedent and consequences, and eventually ascertain methods for improving and measuring service quality in search for competitive advantage. This study will determine the level of satisfaction among the students towards the housing facilities at by Apartment Pelajar Jalan Tun Ali (APJTA) such as the room, cafeteria, laundry system, surau. The study was based on a survey carried out from the questionnaire that is administered involving 160 students. By using the descriptive analysis the level of satisfaction among the students towards the housing facilities are examined. The findings show that the levels of satisfaction among students are mixed. However, majority of students are satisfied with the housing facilities at APJTA. The findings of this study will help the management of APJTA or the to improve their service provided to the students in achieving the students’ satisfaction due to the evaluation of satisfaction level for every variables (facilities).